1284Food insecurity and mental health features and behaviours in adults from Portugal. (2nd September 2021) - Aguiar, Ana; Maia, Isabel; Pinto, Marta; Duarte, Raquel
Abstract: Background: COVID-19 pandemic has been affecting population's health and economies, in which food insecurity appears as important concern, particularly considering its associations with mental health and adverse behaviours. This study explored the relationship between food insecurity and mental health features and behaviours in adults from Portugal. Methods: A cross-sectional study using data from an online survey was performed, including Portugal's residents aged ≥18 years. Data on sociodemographics, behaviours, mental health features and food security status were collected. Food security status was evaluated with the United States Household Food Security Survey Module: Six-item Short Form. Chi-square test or Fisher's exact test, as appropriate, were used to explore the relationship between food security status and categorical variables. Results: Food insecurity prevalence was 6.8%; showed to be significantly higher among less educated individuals (≤12 years of schooling) ( p <0.001), those who were employed and remained since the beginning of the pandemic ( p <0.001) and among those reporting need to be careful about expenses ( p <0.001). Comparing to individuals who were food secure, food insecure participants were more likely to smoke ( p =0.009), to report depressive symptoms ( p <0.001) and anxiety ( p <0.001), measured by the Hospital Anxiety and Depression Scale. Conclusions: From the present study, it can be concluded that the COVID-19 pandemic can affect food security in different subpopulations. Key messages: The findings of this study have several implications for health policy and reinforce the need for investment in contexts of populations vulnerable to food insecurity